My e-journal – exploring the usefulness of personalized access to scholarly articles and services - Jette Hyldegaard; Piet Seiden (Information Research: An International Electronic Journal)
The paper presents the results of a user evaluation study exploring the usefulness of personalized access to scholarly journals and services with regard to the information behaviour of scientists. The aim was to investigate what factors would be critical to personalization, what personalization features would be relevant and to what extent profile and behaviour based personalization would be acceptable. Three providers of personalized access to scholarly journals and services formed the basis of the study. The user group was fourteen doctoral students. Personalization was found to be associated with expectations of increased efficiency compared to traditional searching, emphasizing the need for functionality oriented features such as search alerts. Profile based personalization was to some extent positively associated with reduction of information overload. Various quality indicators were found to affect the perceived reliability of a service, making trust a critical theme when establishing a personalized user experience. The study suggests implications for the digital library when designing for a personalized information environment.